A rare case of primary cardiac diffuse large B-cell lymphoma imaged with 18F-FDG PET/CT: a case report and literature review - Huang, Wenpeng; Zheng, Zuohuan; Zhang, Yongbai; Qiu, Yongkang; Peng, Yushuo; Yang, Qi; Wang, Wei; Kang, Lei (Frontiers in Medicine, 2024)
Background One of the exceptionally rare forms of non-Hodgkin’s lymphoma (NHL) is primary cardiac lymphoma (PCL). The principal clinical manifestation in patients with PCL involves cardiac symptoms resulting from myocardial infiltration by lymphoma, including arrhythmias, heart failure, and chest pain. 18F-FDG PET/CT serves as a reliable and indispensable imaging modality for assessing clinically staging NHL. Case report We present a rare case involving a 72-year-old woman diagnosed with primary intracardiac diffuse large B-cell lymphoma. For further staging, the patient underwent 18F-FDG PET/CT, revealing multiple nodular soft tissue density lesions in the heart and pericardium exhibiting increased FDG metabolism (SUVmax = 12.1). The supradiaphragmatic and infradiaphragmatic segments of the inferior vena cava exhibited irregular morphology with localized nodular changes and increased FDG metabolism in the surrounding area (SUVmax = 9.7). Additionally, multiple enlarged lymph nodes were identified in the left axilla, mediastinum, and adjacent to the abdominal aorta, displaying heterogeneous FDG uptake with an SUVmax of 9.3, indicating lymphoma involvement. The above imaging findings suggested that the mass was a PCL. Hence, the patient underwent a combination of chemotherapy and immunotherapy using R-CDOP (rituximab, cyclophosphamide, liposomal doxorubicin, vincristine, and prednisone). Following two courses of treatment within a span of 2 months, there was a partial remission observed in the cardiac lymphoma and the enlarged lymph nodes. Conclusion The case elucidated in this report contributes to an enhanced understanding of the disease for clinicians, with 18F-FDG PET/CT providing comprehensive insights into the extent of cardiac involvement, as well as the engagement of extracardiac organs and pathologic lymph nodes. The 18F-FDG PET/CT examination not only visually delineates the lesion’s location and extent but also serves as a cornerstone for clinical tumor staging, offering valuable support for treatment monitoring and subsequent follow-up.